Delayed nucleation in lipid particles. Issue 1 (28th November 2019) - Jacoby, Guy; Portnaya, Irina; Danino, Dganit; Diamant, Haim; Beck, Roy
Abstract : Lipid particle crystallization shows non-classical nucleation and growth kinetics and demonstrates a tunable cooperative phase-transition with long characteristic timescales. Abstract : Metastable states in first-order phase-transitions have been traditionally described by classical nucleation theory (CNT). However, recently an increasing number of systems displaying such a transition have not been successfully modelled by CNT. The delayed crystallization of phospholipids upon super-cooling is an interesting case, since the extended timescales allow access into the dynamics. Herein, we demonstrate the controllable behavior of the long-lived metastable liquid-crystalline phase of dilauroyl-phosphatidylethanolamine (DLPE), arranged in multi-lamellar vesicles, and the ensuing cooperative transition to the crystalline state. Experimentally, we find that the delay in crystallization is a bulk phenomenon, which is tunable and can be manipulated to span two orders of magnitude in time by changing the quenching temperature, solution salinity, or adding a secondary phospholipid. Our results reveal the robust persistence of the metastability, and showcase the apparent deviation from CNT. This distinctive suppression of the transition may be explained by the resistance of the multi-lamellar vesicle to deformations caused by nucleated crystalline domains. Since phospholipids are used as a platform for drug-delivery, a programmable design of cargo hold and release can be of great benefit.